Systematic evaluation of petroleum sulfonate: polarity separation and the relationship between its structure and oil recovery properties. Issue 59 (2nd October 2018) - Duan, Yawei; Zhu, Youyi; Fan, Jian; Li, Wenjun; Liu, Xintong; Li, Hongda
Abstract : Petroleum sulfonate actives are efficiently separated and fully characterized, and the relationship between their structure and oil recovery properties is revealed. Abstract : Petroleum sulfonate is one of the most important surfactants in the tertiary oil recovery process. However, its complex composition significantly impedes its evaluation, and the relationship between its structure and oil recovery properties is still unclear. In this study, the actives of petroleum sulfonate are subdivided into seven components, a–g, with different polarities via column chromatography. The structural information of each component is fully characterized. Moreover, the relationship between the oil recovery properties and the structure of the separated components is systematically studied. The results reveal the average relative molecular mass in the range of 560–626, average alkyl side chain containing 36–40 carbon atoms and alkyl chain containing an average of 6 branched chains is the ideal structure for enhancing oil recovery properties. Furthermore, this study provides a reliable evaluation method and reveals the relationship between the structure and oil recovery properties of petroleum sulfonate.